Vegetable crop residues: an opportunity to bridge dry-season feed gaps in sub-Saharan Africa - Orounladji, Boko Michel; Ouattara, Songdah Désiré; Pare, Prosper; Sanogo, Souleymane; Dabire, Der; Sib, Ollo; Assouma, Mohamed Habibou (Frontiers in Animal Science, 2025)
In Burkina Faso, livestock feeding during the dry season is constrained by recurrent quantitative and qualitative deficits of available fodder biomass, a challenge further exacerbated by climate change. One promising strategy to mitigate these shortages is the use of vegetable crop residues (VCR) as supplementary fodder, particularly in areas with intensive vegetable production. This study aimed to characterize the practices of VCR utilization in the vegetable-growing region of Guiriko, in western Burkina Faso. A survey was conducted using a structured questionnaire among 243 farmers in the locality. Principal component analysis followed by hierarchical clustering was used to classify farmers according to their agricultural and livestock practices. This analysis revealed three distinct groups: market gardeners, agro-pastoralists, and livestock farmers. VCR were widely used across all groups as animal feed, with green bean haulms (GBL: 100%) and sweet potato vines (100%) being preferred by nearly all producers. Cucumber residues were also commonly used, particularly by market gardeners (p < 0.05). Most VCR were offered through open grazing, while GBL and cabbage leaves were more frequently dried prior to be stored and fed in barns, especially by agro-pastoralists. Sweet potato vines were often sold and transported to Bobo-Dioulasso for use in urban livestock systems. VCR were primarily allocated to weak livestock, lactating cows, draft animals, and calves, underscoring their functional importance in smallholder systems. These findings highlight the potential of VCR recycling as a means to alleviate dry-season fodder shortages and to support integrated crop-livestock management. Further laboratory analyses are recommended to determine the chemical composition and nutritional value of these residues, which would inform better feeding strategies, improve animal productivity, and contribute to reducing greenhouse gas emissions per unit of livestock product.